2020
DOI: 10.1002/2211-5463.13064
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ1 inhibition combined with inhibition of apoptosis and necroptosis increases cartilage matrix synthesis in IL‐1β‐treated rat chondrocytes

Abstract: We found that inhibition of PLCγ1 phosphorylation by U73122 improved cartilage matrix synthesis in IL‐1β‐treated rat chondrocytes. However, it also increased cell apoptosis and necroptosis, which reduced the effect on cartilage matrix synthesis. Inhibition of programmed cell death by simultaneous treatment with apoptosis and necroptosis inhibitors increased chondrocyte proliferation and further enhanced cartilage matrix synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…The immunofluorescence experiments, using an anti‐PI‐PLC γ1 antibody, recognizing an epitope mapping at the C‐terminal of the protein, show a significant decrease of PI‐PLC γ1. The decreased of this protein seems desirable in OA, previously has been described that the inhibition of PI‐PLC γ1 stimulates the production of ECM in rat chondrocytes challenged with proinflammatory cytokine IL‐1β 35 . Moreover, the intra‐articular injection of PI‐PLC γ1 inhibitor in rat OA joint showed a decrease of PI‐PLC γ1 phosphorylation level, giving a protective action on chondrocytes 36 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The immunofluorescence experiments, using an anti‐PI‐PLC γ1 antibody, recognizing an epitope mapping at the C‐terminal of the protein, show a significant decrease of PI‐PLC γ1. The decreased of this protein seems desirable in OA, previously has been described that the inhibition of PI‐PLC γ1 stimulates the production of ECM in rat chondrocytes challenged with proinflammatory cytokine IL‐1β 35 . Moreover, the intra‐articular injection of PI‐PLC γ1 inhibitor in rat OA joint showed a decrease of PI‐PLC γ1 phosphorylation level, giving a protective action on chondrocytes 36 .…”
Section: Discussionmentioning
confidence: 94%
“…The decreased of this protein seems desirable in OA, previously has been described that the inhibition of PI-PLC γ1 stimulates the production of ECM in rat chondrocytes challenged with proinflammatory cytokine IL-1β. 35 Moreover, the intra-articular injection of PI-PLC γ1 inhibitor in rat OA joint showed a decrease of PI-PLC γ1 phosphorylation level, giving a protective action on chondrocytes. 36 In our context, the decreased amount of protein means a lower amount of active PI-PLC γ1 enzyme, which results in a protective action in OA.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing ROS level was detected in chondrocytes with PUM2 overexpression in our experiments. It has been reported that the excessive accumulation of ROS represents the intracellular oxidative stress, and maybe mediate IL-1β-induced cell apoptosis of chondrocytes [ 33 , 34 ]. Oxidative stress has been demonstrated to participate in the impairment of chondrocytes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…If we further relate our findings to those from other studies with respect to fibroblasts and epithelial cells, we are apparently publishing pioneering work on how Z-VAD affects cell viability and the inflammatory response to TNFα. Most research is focused on inflammation-induced cell viability and ROS production, for which Z-VAD was found to increase the sensitivity of L929 [ 41 ] and rat chondrocytes [ 42 ] to inflammatory clues. In our study, TNFα alone or in combination with Z-VAD had no negative impact on the metabolic activity of fibroblastic cells.…”
Section: Discussionmentioning
confidence: 99%